Detour: Bodies, memories, and mobilities in and around the home. Issue 6 (1st November 2020) - Ratnam, Charishma; Drozdzewski, Danielle
ABSTRACT: The word detour denotes taking adifferent direction and/or adeviating pathway– especially from aconsidered norm. While the connotations of taking adetour are not always negative, the idea of movement away from, or against an assumed trajectory indicates achange in direction. In this paper, we pursue both what prompts this changed direction and the products of the detour itself. We follow the detours of Sri Lankan refugees and asylum seekers enacted during walk-along and in-depth interviews in their homes in Sydney, Australia. The walks provided opportunities for 'talk' with 'encounter'; the embodied, emplaced, and habitual movements of the participants illuminated the interplay of memory with place. Their mobilities– across borders or through routine movements in everyday spaces– opened multiple conduits of encounter. We use the notion of detour to think with and think through their facilitating and ensuing mobilities, and their relationship to memory, identity, and place. Our theorisation of detour pushes mobilities scholarship further, by engaging with bodies, memories, and homes across multiple spatial, temporal, and lifecourse trajectories.